The influence of deans’ transactional leadership behaviors on research productivity in public universities: The mediating effect of workplace learning capability - Ayetenew Abie; Getnet Demissie Bitew; Solomon Melese Mengistie (Bahir Dar Journal of Education, 2024)
This study examined the effect of transactional leadership behaviors on research productivity in public universities, with organizational learning capability serving as a mediating factor. A quantitative research approach focusing on correlational design was utilized. Data were collected through a survey questionnaire administered to 519 respondents. Both measurement and structural model analyses were conducted, with deans, colleges, and individual academics serving as units of analysis. The findings revealed that deans’ contingent reward leadership behaviors significantly and positively influenced the research productivity of academics and colleges, even when controlling for workplace learning capability. Furthermore, the study demonstrated that deans’ contingent rewards and active-by-exception behaviors significantly and positively impacted workplace learning capability, accounting for 44.5% of the variance, with moderate and small effect sizes, respectively. Additionally, organizational learning capability exhibited a significant positive effect, explaining 54% of the variance in research productivity and demonstrating a moderate effect size, which indicates an unexplained variance of 46%. Bootstrapping tests confirmed that workplace learning capability partially and fully mediates the relationship between deans’ transactional leadership behaviors and research productivity. Consequently, it is imperative for college deans to enhance their contingent reward leadership behaviors and foster workplace learning capabilities to maximize their impact on research productivity.